PENERAPAN PENGAJARAN DAN PEMBELAJARAN KONTEKSTUAL(CTL) DALAM PENGAJARAN KETERAMPILAN BAHASA INGGRIS - Noviati, Noviati (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstractThe main objective of this study is to overcome the problems found in teaching Integrated Skills using Contextual Teaching and Learning (CTL). These problems include: Content, Teaching Methods, and the passivity of the students in the class. Research conducted using action research. The population of this research is a high school student Bina Warga 2 Palembang academic year 2008/2009. There are 16 classes, but this study only takes this because researcher has only been teaching two classes. While other classes taught by other teachers. The main source of this research is supported Â by researchers and teachers who made observations when done in teams. This study not only observed but also questionnaires and interviews to determine students progress in line with the problems. In the first period, the first issue (material) and the second issue (teaching methods) are almost resolved properly. Almost all students said that they felt happy and get the ease of Â learning to use materials related to their lives and experiences, as well as related from one skill to the second period is another problem. At the first and second can be addressed properly because all the students said that they feel happy and get the ease of learning to use material Â relating from one skill to another. In the third period students have easy and are happy with the material that relates to their lives and experiences and integrate the skills learned. For the problem of studentsâ passivity, it is solely due to the personal problems of students.Keywords : Contextual Teaching and Learning (CTL), Integrated English Skills, Learning